Providing nutrition - Conaway, Deborah Jean; Studio Three Productions (Philadelphia, Pa. : Lippincott, 1997)
(Producer) The viewer will learn to assist with feeding, including how to assist clients with visual, swallowing or mobility impairments. The video also demonstrates how to administer enteral nutrition, intermittently and continuously
Videocassette is available at Koleksi Media, Perpustakaan HUKM
Keywords: Enteral Nutrition -- nursing; Nursing Assessment -- methods; Intubation, Gastrointestinal -- nursing; Diet -- nursing; Nutrition